A Hydrolyzed Soybean Protein Enhances Oxidative Stress Resistance in C. elegans and Modulates Gut–Immune Axis in BALB/c Mice - Jun Liu; Yansheng Zhao; Fei Leng; Xiang Xiao; Weibo Jiang; Shuntang Guo (Antioxidants)
Soy protein isolate (SPI) is a high-purity protein from defatted soybeans, providing emulsifying and gelling functions for plant-based foods and supplements. Hydrolysis can facilitate the production of bioactive small-molecule proteins or peptides with potential functional applications. In this study, 20% hydrolyzed soy protein (20% HSP) was prepared from SPI, and the effects of 20% HSP and SPI on alleviating oxidative stress in Caenorhabditis elegans (C. elegans) and regulating immune–gut microbiota in cyclophosphamide (CTX)-induced immunocompromised BALB/c mice were investigated. In C. elegans, both SPI and 20% HSP (300 μg/mL) enhanced locomotive activities, including body bending and head thrashing, and improved oxidative stress resistance under high glucose conditions. This improvement was mediated by increased antioxidant enzyme activities (SOD, CAT, and GSH-Px), while malondialdehyde (MDA) content was reduced by 60.15% and 82.28%, respectively. Both of them can also significantly extend the lifespan of normal C. elegans and paraquat-induced oxidative stress models by inhibiting lipofuscin accumulation. This effect was mediated through upregulation of daf-16 and suppression of daf-2 and akt-1 expression. In immunocompromised mice, 20% HSP alleviated CTX-induced immune dysfunction by increasing peripheral white blood cells and lymphocytes, attenuating thymic atrophy, and reducing hepatic oxidative stress via MDA inhibition. Gut microbiota analysis revealed that 20% HSP restored microbial balance by suppressing Escherichia-Shigella and enriching beneficial genera, like Psychrobacter. These findings highlight 20% HSP and SPI’s conserved anti-aging mechanisms via daf-16 activation in C. elegans and immune–gut modulation in mice, positioning them as plant-derived nutraceuticals targeting oxidative stress and immune dysregulation.